The importance of acoustic radiation force impulse (ARFI) elastography in the diagnosis and clinical course of acute pancreatitis - Kaya, Muhsin; Değirmenci, Serdar; Göya, Cemil; Tuncel, Elif Tuba; Uçmak, Feyzullah; Kaplan, Mehmet Ali (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Acute pancreatitis (AP) is characterized by acute inflammation of the pancreas and it has a highly variable clinical course. The aim of our study was to evaluate the value of acoustic radiation force impulse (ARFI) elastography in the diagnosis and clinical course of AP. Materials and Methods: Consecutive patients with a diagnosis of AP (patients group) and healthy subject (control group) were prospectively enrolled to the study. Demographic features and clinical, laboratory, and radiological data were recorded. Virtual Touch Tissue Quantification (VTQ) was used to implement ARFI elastography. The tissue elasticity is proportional to the square of the wave velocity (SWV). Results: A total of 108 patients (age, 57±1.8 y) and 79 healthy subjects (age, 53.6±1.81 y) were included in the study. There were 100 (92.5%) edematous and 8 (7.4%) necrotizing AP. The mean SWV was significantly higher in the patient group than in the control group (2.43±0.08 vs. 1.27±0.025 m/s, p Conclusion: ARFI elastography may be a feasible method for the diagnosis of AP, but it has no value for the prediction of clinical course of AP. Cite this article as: Kaya M, Değirmenci S, Göya C, Tuncel ET, Uçmak F. The importance of acoustic radiation force impulse (ARFI) elastography in the diagnosis and clinical course of acute pancreatitis. Turk J Gastroenterol 2018; 29: 342-7.